P–088 Sexual functioning is impaired in cancer survivors after cancer therapy. (6th August 2021) - Reiser, E; Vomstein, K; Hofer-Tollinger, S; Pinggera, G; Strassgschwandtner, E; Zippl, A L; Böttcher, B; Toth, B
Abstract: Study question: Is impaired sexual functioning correlated to sperm quality in cancer survivors? Summary answer: Erectile dysfunction affects 25.0% of cancer survivors, independent of sperm quality. 22.9% of patients show symptoms consistent with a reduced testosterone level. What is known already: Gonadotoxic treatment in male cancer patients can end up in reversible or permanent impaired spermatogenesis, testosterone insufficiency, and sexual dysfunction. Study design, size, duration: In this prospective single-center study, sexual functioning was assessed in male cancer survivors, who underwent sperm cryopreservation at the Department of Gynecological Endocrinology and Reproductive Medicine, Medical University Innsbruck, Austria from 01/2010 to 12/2018. Sexual functioning was assessed between 03–12/2020 via two questionnaires: Aging Male Score (AMS) and International Index of Erectile Function (IEEF-EF). Participants/materials, setting, methods: Thirty-five cancer survivors (testicular cancer: n = 16 [45.7%], hematological malignancies: n = 15 [42.9%], others: n = 4 [n = 11.4%]) filled in two questionnaires (AMS and IEEF-EF) during routine follow-up visit at the Department of Gynecological Endocrinology and Reproductive Medicine, Medical University Innsbruck and the Department of Urology, Medical University Innsbruck, Austria. Moreover, sperm quality was assessed and normozoospermia was defined in accordance with the 2010 WHO criteria (sperm concentration ≥15 million/mL, progressive motility ≥32%, and ≥4% normal morphology). Main results and the role of chance: Mean age at sperm cryopreservation and follow-up visit was 25.1±4.2 and 31.9±6.3 years, respectively with a mean follow-up time of 81.4±12.5 months. Rate of erectile dysfunction was low (75.0% no dysfunction, 15.6% low dysfunction, 3.1% low-moderate dysfunction, 3.1% moderate, 3.1% severe dysfunction). Moreover, AMS score indicated no, low, moderate and severe symptoms consistent with a low testosterone level in 77.1%, 8.6%, 2.9%, and 2.9% of patients, respectively. Oligozoospermia was observed in up to 48% of the patients with TM and in only 23% patients with HM. Patients with TM showed significantly reduced sperm count (18.7 × 106/mL [5.3–43.0]) and total sperm count (42.4 × 106/ejaculate [13.3–108.5]) compared to HM (p = 0.03). There was no difference in sexual functioning between patients with HM or TM. Sexual functioning did no correlate with sperm count, progressive motility or morphology. Limitations, reasons for caution: Although the study may be limited by its small sample size, it is the first to assess a correlation of sperm quality and sexual dysfunction in cancer survivors. Wider implications of the findings: As every fourth male cancer patient suffers from impaired sexual functioning after gonadotoxic treatment, this important topic should be addressed in clinical and scientific future. Future studies should focus on both, somatic and psychosomatic reasons for sexual dysfunction. Trial registration number: none